Eptinezumab administered intravenously, subcutaneously, or intramuscularly in healthy subjects and/or patients with migraine: Early development studies. (11th October 2022) - Baker, Brian; Shen, Vivienne; Cady, Roger; Ettrup, Anders; Larsen, Frank
Objective: To report the safety, tolerability, and pharmacokinetics/pharmacodynamics (PK/PD) of eptinezumab using intravenous (IV) infusion compared to other routes of administration from two phase 1 trials. Methods: Study 1 (NCT01579383) and Study 2 (ACTRN12615000531516) were double-blind, placebo-controlled, randomized trials. Study 1 singly administered ascending doses of eptinezumab 1–1000 mg IV infusion or 100 mg subcutaneous (SC) injection to healthy adults on day 1 ( n = 60); in a second part, eptinezumab 300 mg IV + sumatriptan 6 mg SC was administered to healthy adults and patients with migraine ( n = 18). Study 2 administered eptinezumab 100 or 300 mg intramuscular (IM), 100 mg SC, or 100 mg IV to healthy adults on days 1 and 84 ( n = 60). Results: No withdrawals due to treatment-emergent adverse events (TEAEs) were reported due to IV administration, with IV generally reporting TEAEs similar to placebo. The pharmacokinetics of eptinezumab were as expected for a monoclonal antibody, with the 100 mg and 300 mg IV doses exhibiting higher C max and shorter t max compared to identical SC and IM doses. Discussion: These phase 1 safety and tolerability data supported eptinezumab intravenous infusions at 100 and 300 mg; both were approved for migraine prevention, were well tolerated, had low immunogenicity and rapid attainment of high plasma concentrations.